Impact of platform switching on marginal peri‐implant bone‐level changes. A systematic review and meta‐analysis. Issue 3 (20th January 2014) - Strietzel, Frank Peter; Neumann, Konrad; Hertel, Moritz
Abstract Objective To address the focused question, is there an impact of platform switching (PS) on marginal bone level (MBL) changes around endosseous implants compared to implants with platform matching (PM) implant‐abutment configurations? Material and methods A systematic literature search was conducted using electronic databases PubMed, Web of Science, Journals@Ovid Full Text and Embase, manual search for human randomized clinical trials (RCTs) and prospective clinical controlled cohort studies (PCCS) reporting on MBL changes at implants with PS‐, compared with PM‐implant‐abutment connections, published between 2005 and June 2013. Results Twenty‐two publications were eligible for the systematic review. The qualitative analysis of 15 RCTs and seven PCCS revealed more studies (13 RCTs and three PCCS) showing a significantly less mean marginal bone loss around implants with PS‐ compared to PM‐implant‐abutment connections, indicating a clear tendency favoring the PS technique. A meta‐analysis including 13 RCTs revealed a significantly less mean MBL change (0.49 mm [CI95% 0.38; 0.60]) at PS implants, compared with PM implants (1.01 mm [CI95% 0.62; 1.40] (P < 0.0001). Conclusions The meta‐analysis revealed a significantly less mean MBL change at implants with a PS compared to PM‐implant‐abutment configuration. Studies included herein showed an unclear as well as high risk of bias mostly, and relatively short follow‐up periods. The qualitative analysis revealed a tendency favoring the PS technique to prevent or minimize peri‐implant marginal bone loss compared with PM technique. Due to heterogeneity of the included studies, their results require cautious interpretation.